Hydrolysis of tannins by tannase immobilized onto magnetic diatomaceous earth nanoparticles coated with polyaniline. (May 2018) - de Lima, Juliana Silva; Cabrera, Mariana Paola; de Souza Motta, Cristina Maria; Converti, Attilio; Carvalho, Luiz B.
Abstract: Responsible for hydrolysis of tannins present in several beverages, tannase is an industrial enzyme of the great potential for applications in the food industry. Tannase was covalently immobilized onto magnetic nanoparticles composed of diatomaceous earth coated with polyaniline (mDE-PANI-TANNASE). This enzyme derivative showed 41% of residual specific activity, higher optimum temperature (40 °C) than the free enzyme (30 °C) and proved to be more thermostable at 40 °C, whereas both preparations presented the same optimum pH (6.0). The apparent Km values for the free and immobilized enzyme were statistically different (p = 0.03) and equal to, respectively, 18 ± 7 μM and 10 ± 2 μM. mDE-PANI-TANNASE after ten reuses and 90 days of storage at 4 °C kept as much as 66% and 71% of its initial activity, respectively. Even though the tannins content of boldo tea was reduced by only 23–25% after 120 min treatment with either free or immobilized enzyme, mDE-PANI-TANNASE has the advantage of being simply recovered and recycled from the reaction mixture by an outer magnet, thus preventing contamination of the treated tea. Graphical abstract: Highlights: Magnetic diatomite nanoparticles coated with PANI as carrier to tannase immobilization First biocatalyst applied to tannins hydrolytic process in boldo tea Thermal stability of the immobilized tannase was increased 23% over the free enzyme. Magnetic immobilized tannase showed 66% residual activity after 10th cycles of reuse. Magnetic immobilized tannase was able to remove 25% tannin from the boldo tea.